2005
DOI: 10.1111/j.0105-2896.2005.00271.x
|View full text |Cite
|
Sign up to set email alerts
|

Human immunosenescence: is it infectious?

Abstract: Morbidity and mortality due to infectious disease is greater in the elderly than in the young, at least partly because of age-associated decreased immune competence, which renders individuals more susceptible to pathogens. This susceptibility is particularly evident for novel infectious agents such as in severe acute respiratory syndrome but is also all too apparent for common pathogens such as influenza. Many years ago, it was noted that the elderly possessed oligoclonal expansions of T cells, especially of C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

16
320
2
4

Year Published

2007
2007
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 379 publications
(342 citation statements)
references
References 70 publications
16
320
2
4
Order By: Relevance
“…One aspect should be mentioned, and that is that overall changes in telomere length could be the result of changes in subsets of cells. In this context it is of interest that expansion of blood CD8 + T lymphocytes is associated with all-cause mortality (Wikby et al, 2002;Pawelec et al, 2005). CD8 + CD28 − T lymphocytes have telomeres that are shorter than those of other white blood cells from the same individual (Monteiro et al, 1996;Effros et al, 1996); this may be connected to the observation that loss of CD28 expression is also associated with loss of ability of T lymphocytes to upregulate telomerase activity (Valenzuela and Effros, 2002).…”
Section: Do Telomere Biology and Telomerase Activity Determine Aging?mentioning
confidence: 99%
“…One aspect should be mentioned, and that is that overall changes in telomere length could be the result of changes in subsets of cells. In this context it is of interest that expansion of blood CD8 + T lymphocytes is associated with all-cause mortality (Wikby et al, 2002;Pawelec et al, 2005). CD8 + CD28 − T lymphocytes have telomeres that are shorter than those of other white blood cells from the same individual (Monteiro et al, 1996;Effros et al, 1996); this may be connected to the observation that loss of CD28 expression is also associated with loss of ability of T lymphocytes to upregulate telomerase activity (Valenzuela and Effros, 2002).…”
Section: Do Telomere Biology and Telomerase Activity Determine Aging?mentioning
confidence: 99%
“…Importantly, later longitudinal studies in Sweden, examining a representative sample of the very elderly not selected for good health, the majority of whom were actually frail, revealed that the IRP, including CMV seropositivity, still predicted mortality (Pawelec et al, 2005). More recent studies using this longitudinal "NONA" population, now over 90 yr of age, suggested that the number of different clones expanding in the elderly, and particularly the later clonal attrition observed to occur in IRP individuals, was highly correlated with 2, 4 and 6 year survival in this population (Hadrup et al, 2006).…”
mentioning
confidence: 99%
“…Huppert et al, 2005) we asked whether CMV had an over-riding effect on specific immunity in this population as well. We also examined a second persistent herpes virus, EBV, which was known to have a similar, but lesser effect, in the Swedish population (Pawelec et al, 2005).…”
mentioning
confidence: 99%
“…Some of the most important characteristics of clonotypic immunity in ageing are compatible with this assumption since it is characterized by a decrease of virgin T cells and by the filling up of the immunological space by "megaclones" of memory T cells, resistant to apoptosis and capable of exerting negative regulatory functions (Franceschi et al, 2000a;De Martinis et al, 2005;Pawelec et al, 2004Pawelec et al, , 2005. Concomitantly, the antigenic load results in the progressive generation of inflammatory responses involved in agerelated diseases, for which the name "inflamm-aging" has been proposed (Franceschi et al, 2000c).…”
mentioning
confidence: 89%